Design of steel-reinforced concrete structures implementation of calculation algorithms according to the norms relevance - Abilmazhenov, Талғат; Bekkalieva, Назерке (Рroblems of engineering and professional education, 2023)
Briefly covers the problems about implementation in Kazakhstan standards of design a new calculation rules of steel-concrete composite structures. Analyze existing Kazakhstan standards of design of these elements and their further development. A comparison of the developed regulations with best international standards.The possibilities of algoritmically calculation of steel-concrete composite structures by the example of the method of calculation of steel-concrete composite plate.